The Washingtons : George and Martha, "join'd by friendship, crown'd by love" - Fraser, Flora (Alfred A. Knopf, 2015)
"A full-scale portrait of the marriage of the father and mother of our country--and of the struggle for independence that he led"--Dust jacket flap.